2009
DOI: 10.1148/radiol.2531081923
|View full text |Cite
|
Sign up to set email alerts
|

Wide-necked Intracranial Aneurysms: Treatment with Stent-assisted Coil Embolization during Acute (<72 Hours) Subarachnoid Hemorrhage—Experience in 61 Consecutive Patients

Abstract: Stent-assisted coil embolization is a feasible method for the endovascular treatment of wide-necked intracranial aneurysms that are difficult to treat surgically or with balloon-assisted embolization during acute SAH. The risk of subsequent rerupture of the aneurysm seems to be reduced for aneurysms treated early compared with that for nonsecured aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(127 citation statements)
references
References 25 publications
6
118
3
Order By: Relevance
“…In this series, 82.2% patients were of good-grade (Hunt-Hess grade I or II) and this may associated with our favorable clinical outcomes. Contrast to 2.8% to 5.1% complication rate in other endovascular series (14,20), there was no procedure-related complication in our series.…”
Section: █ Discussioncontrasting
confidence: 90%
“…In this series, 82.2% patients were of good-grade (Hunt-Hess grade I or II) and this may associated with our favorable clinical outcomes. Contrast to 2.8% to 5.1% complication rate in other endovascular series (14,20), there was no procedure-related complication in our series.…”
Section: █ Discussioncontrasting
confidence: 90%
“…Previous studies showed initial complete occlusion rates from 27-73 % [37][38][39][40] in treating aneurysms by stentassisted coiling; compared with these studies, our results appeared moderate (63 % in group A and 44 % in group B). The cases included in the present series were all widenecked and ruptured aneurysms, thus posing a challenge to angiographic occlusion.…”
Section: Discussioncontrasting
confidence: 65%
“…58,60 In this setting, plagued by the specter of early rerupture, the cerebrovascular neurosurgeon must safely expose these complex aneurysms and adjacent vital perforators while navigating an edematous, "angry" brain.…”
Section: Neurosurg Focus 33 (2):e9 2012mentioning
confidence: 99%
“…Despite the preponderance of endovascular approaches to these lesions, 15,36,45,53,58 some may remain refractory to safe endovascular management. In several cases we reviewed endovascular treatment had previously been attempted without success.…”
Section: Looking Forwardmentioning
confidence: 99%
See 1 more Smart Citation